answersLogoWhite

0


Best Answer

Perform the indicated subtraction.

12 - 9 = 3

User Avatar

Wiki User

โˆ™ 2013-02-26 01:15:45
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: How do you simplify -9 plus 12?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

Simplify 6a plus 9 over 12?

a = 1/2


How do you simplify 6x plus 9 plus 2x?

6x + 9 + 2x = 8x + 9


How you simplify expression 5 plus 2x plus 9?

2x


What is twelfth of 9?

It is 9/12, which you can simplify if required.


How do i Add and simplify 916 plus 12?

67


What is 4m plus 9 plus 5m-12 equals 42 simplify?

4m + 9 + 5m - 12 = 42 Combining like terms to both sides:9m=42+12-9=>9m=45 divide both side by 9:m=5;


Simplify 4 9 plus 3 7?

When you simplify 49 plus 37 (49+37), the result is 86.


Can you simplify this 17.2 plus 3.1y plus 4.2y plus 9?

17.2 + 3.1y + 4.2y + 9 = 7.3y + 26.2


How do you simplify negative 3 plus negative 12?

-3 + -12 = -15


How do you simplify the expression 9-a plus 6?

15


How do you simplify 2 cubed plus 3 squared?

Answer: 12


How do you simplify 2x plus 12?

You can factor it, if you consider that simpler.


Simplify this expression 4p plus 9 plus-7pplus 2?

11-3p


Simplify 7x plus 7 plus 6x - 9?

7x + 7 + 6x - 9 = 13x - 2


Simplify this expression 4p plus 9 plus 7p plus 2 equals?

11p+11


Simplify 5xsquared plus 14x 3 xsquared 9?

It is: 2xsquared+14x-9


How can you simplify and slove this equation 4m plus 9 plus 5m minus 12 equals 42?

4m + 9 + 5m - 12 = 42 9m -3 = 42 9m = 42 + 3 9m = 45 m = 5


Simplify 4p plus 9 plus -7p plus 2?

4p + 9 + (-7p) + 2 = 4p - 7p + 9 + 2 = -3p + 11


Simplify -3x-6x plus x?

-9


Simplify 5 -9 plus 13 plus -1?

The simple form of the equation 5 - 9 + (-1) is -5.


Simplify 3x - 2y plus 9 plus 9y - x?

3x-2y+9+9y-x = 2x+7y+9


What is -3 plus -9?

-12


Simplify x plus 5 plus 4?

x + 5 + 4 = x + 9


How can I simplify 23 plus 5(9 plus 1)?

It is the same as 23+50 = 73


Simplify -12 plus 6-10-6 plus 15?

-12 + 6 - 10 - 6 +15 = -7